The Emerging Biomarkers in Chronic Obstructive Pulmonary Disease: A Narrative Review - Kaitlin M. Phillips; Philip F. Lavere; Nicola A. Hanania; Muhammad Adrish (Diagnostics)
The burden of chronic obstructive pulmonary disease (COPD) is increasing, especially for women in low-to-middle income countries. Biomarkers provide ever-increasing diagnostic precision for COPD and show promise for primary, secondary, and tertiary disease prevention. This review describes emerging applications for biomarkers in COPD, especially as they align with the Global Initiative for Chronic Obstructive Lung Disease (GOLD) emphasis on prevention, early diagnosis, and response to therapy. These biomarkers include blood eosinophils; IgE; C-reactive protein; fibrinogen; procalcitonin; interleukins 6, 8, and 33; tumor necrosis factor alpha; and soluble receptor for advanced glycated products (sRAGE). They have been used in various ways to identify COPD endotypes, predict exacerbations, predict mortality, and monitor the response to therapy. The fraction of exhaled nitric oxide (FENO) is increasingly studied in eosinophilic COPD endotypes and can be a diagnostic and predictive non-invasive biomarker. Imaging biomarkers, especially the quantitative computerized tomography (QCT) assessment of airway remolding, functional small airway disease, air trapping, lung function, and volume surrogates, all serve as non-invasive biomarkers for screening, early detection, and disease progression. Biomarkers facilitate all the phases of COPD care from detecting early airflow obstruction to predicting exacerbation and mortality. Biomarkers will be increasingly used as precise diagnostic tools to improve the COPD outcomes. The aim of this narrative review is to summarize the recent investigations in COPD biomarkers and their clinical applications.